2010
DOI: 10.1007/s00418-010-0762-2
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens regulate the expression of NHERF1 in normal colon during the reproductive cycle of Wistar rats

Abstract: In breast cancer cell lines, the Na(+)/H(+) exchanger regulator factor 1 (NHERF1) gene is regulated at the transcriptional level by estrogens, the protein expression levels correlate with the presence of estrogen receptors and the effect is blocked by anti-estrogens. However, there is limited information regarding the regulation of NHERF1 by estrogens in normal colon tissue. The NHERF1 protein has an important role in the maintenance of the intestine ultrastructure. NHERF1-deficient mice showed defects in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The tumor density was increased in female mice of both genotypes, whereas adenomas developed at a similar rate in both genders in Apc Min/+ mice and yet again with female predominance in Apc Min/+ NHERF1 −/− double-mutant mice. One correlation is the regulation of NHERF1 expression by estrogen receptor [47] and its variation in rodent intestine during estral cycle [48]. Although this could explain the limited growth of adenomas in Apc Min/+ females by a suppressor effect of NHERF1, more studies are necessary to address the increased tumor incidence in Apc Min/+ females.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor density was increased in female mice of both genotypes, whereas adenomas developed at a similar rate in both genders in Apc Min/+ mice and yet again with female predominance in Apc Min/+ NHERF1 −/− double-mutant mice. One correlation is the regulation of NHERF1 expression by estrogen receptor [47] and its variation in rodent intestine during estral cycle [48]. Although this could explain the limited growth of adenomas in Apc Min/+ females by a suppressor effect of NHERF1, more studies are necessary to address the increased tumor incidence in Apc Min/+ females.…”
Section: Discussionmentioning
confidence: 99%
“…In the positive carcinoma cases, the expression of NHERF1 was mainly cytoplasmic as was previously described for breast cancer cell lines [24]. NHERF1 expression is stimulated by estrogens in breast cancer cells and normal colon tissue; however, its regulation by estrogens in colon cancer is still unknown [8,28]. Here, we tested the hypothesis that NHERF1 could act as a tumor suppressor gene in colon cancer as a mediator of the estrogens' protective actions in colon carcinogenesis.…”
Section: Introductionmentioning
confidence: 71%
“…In normal rat colon, the expression of NHERF1 fluctuates during the estral cycle in response to E2 levels in plasma indicating the regulation of NHERF1 by estrogens in this tissue [8]. A recent report in human samples describes the absence of NHERF1 expression in human adenomas and the ectopic cytoplasmic expression of NHERF1 in about 50% of human adenocarcinoma specimens [24].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Due to observations that NHERF1 may act as a tumour suppressor or as oncogene (Pan et al 2006;Shibata et al 2003) and that treatment with estrogens prevents colon carcinogenesis, a potential role of NHERF1 in colon carcinogenesis needed to be determined. Cuello-Carrion et al (2010), therefore used the colon and uterus of cycling rats to study NHERF1 expression during the estral cycle. During the estrous stage the authors found oestrogen-dependent expression of NHERF1 in the colon.…”
Section: Moleculesmentioning
confidence: 99%